Performance and Emission characteristics of IC engine using modified coated Piston Head - Magadum, Arun; S. N. Sridhara, Dr. (International Journal of Engineering and Technology, 2018)
Internal s combustion s engines s have s been s a s relatively s inexpensive s and s reliable s source s of s power s for s applications s ranging s from s domestic s use s to s large s scale s industrial s and s transportation s applications s for s most s of s the s twentieth s century. s DI s Diesel s engines, s having s the s evident s benefit s of s a s higher s thermal s efficiency s than s all s other s engines, s have s served s for s both s light- s duty s and s heavy-duty s vehicles. s In s DI s diesel s engines, s swirl s can s increase s the s rate s of s fuel-air s mixing. s Swirl s interaction s with s compression s induced s squish s flow s increases s turbulence s levels s in s the s combustion s bowl, s promoting s mixing. s It s is s evident s that s the s effect s of s geometry s has s a s negligible s effect s on s the s airflow s during s the s intake s stroke s and s early s part s of s the s compression s stroke. s But s when s the s piston s moves s towards s Top s Dead s Centre s (TDC), s the s bowl s geometry s has s a s significant s effect s on s air s flow s thereby s resulting s in s better s atomization, s better s mixing s and s better s combustion. s In s CI s engine s piston s shapes s on s crown s is s flat s and s concave s combustion s chamber, s with s this s geometry s we s have s been s running s the s engine. s But s here s air s fuel s ratio s mixture s cannot s mix s properly. s To s avoid s this s we s make s piston s geometry s changes. s The s main s object s of s this s project s is s to s investigate s the s performance s technique s to s enhance s the s air s swirl s to s achieve s betterment s in s engine s performance s and s emission s in s a s direct s injection s (DI) s single s cylinder s diesel s engine. s In s order s to s achieve s the s swirl s intensities s in s the s cylinder, s changes s on s the s piston s crown s has s been s selected. s To s increase s the s swirl, s series s of s experiments s were s conducted s like s 2 s toroidal s grooves s piston, s 4 s toroidal s grooves s piston, s 6 s toroidal s grooves s piston s on s piston s crown s and s compare s the s results s with s normal s piston s valuesÂ Â